Ivabradine treatment prevents dobutamine-induced increase in heart rate in patients with acute decompensated heart failure. Issue 9 (September 2015) - Cavusoglu, Yuksel; Mert, Ugur; Nadir, Aydin; Mutlu, Fezan; Morrad, Bektas; Ulus, Taner
Abstract : Background: Ivabradine is a heart rate (HR)-lowering agent acting by inhibiting the If -channel. Dobutamine does increase the HR and has some deleterious effects on myocardium. So, we aimed to evaluate whether ivabradine treatment blunts a dobutamine-induced increase in HR. Methods: The main study population consisted of 58 acute decompensated heart failure patients requiring inotropic support with left-ventricular ejection fraction below 35%, who were randomized to ivabradine ( n = 29) or control ( n = 29). All patients underwent Holter recording for 6 h and then dobutamine was administered at incremental doses of 5, 10 and 15 μg/kg/min, with 6-h steps. Holter recording was continued during dobutamine infusion. Ivabradine 7.5 mg was given at the initiation of dobutamine and readministered at 12 h of infusion. Also, a nonrandomized beta-blocker group with 15 patients receiving beta-blocker was included in the analysis. Control and beta-blocker groups did not receive ivabradine. Results: In the control group, mean HR gradually and significantly increased at each step of dobutamine infusion (81 ± 11, 90 ± 16, 97 ± 14 and 101 ± 16 b.p.m., respectively; P = 0.001), whereas no significant increase in HR was observed in the ivabradine group (82 ± 17, 82 ± 15, 85 ± 14 and 83 ± 12 b.p.m., respectively; P = 0.439). Mean HR was also found to significantly increase during dobutamine infusion in the beta-blocker group (75 ± 13, 82 ± 13, 86 ± 14 and 88 ± 13 b.p.m., respectively; P = 0.001). The median increase in HR from baseline was significantly higher in the control group compared to those in the ivabradine group (5 vs. 2 b.p.m.; P = 0.007 at first step, 13 vs. 5 b.p.m.; P = 0.001 at second step and 18 vs. 6 b.p.m.; P = 0.0001 at third step of dobutamine, respectively). Conclusions: Ivabradine treatment prevents dobutamine-induced increase in HR and may be useful in reducing HR-related adverse effects of dobutamine.